Application of conductive PPy/SF composite scaffold and electrical stimulation for neural tissue engineering. (October 2020) - Zhao, Yahong; Liang, Yunyun; Ding, Supeng; Zhang, Kunyu; Mao, Hai-quan; Yang, Yumin
Abstract: Electrical stimulation (ES) with conductive polymers can dramatically enhance neurite outgrowth and promote neural regeneration. However, besides ES, the practical applications of neural repair is also highly dependent on the nerve cell functionality and response to substrate conductivity. Therefore, the combination of the ES and suitable materials, such as tissue scaffolds, has been applied to facilitate treatment of neural injuries and demonstrated great potential in peripheral nerve regeneration. In this study, polypyrrole/silk fibroin (PPy/SF) conductive composite scaffold was fabricated by 3D bioprinting and electrospinning. Schwann cells seeded on these scaffolds were electrically stimulated and hence demonstrated enhanced viability, proliferation and migration, as well as upregulated expression of neurotrophic factors. Furthermore, the constructed PPy/SF conductive nerve guidance conduits accompanying with ES could effectively promote axonal regeneration and remyelination in vivo. Moreover, we found that the MAPKs signal transduction pathway was activated by ES at the conductive conduit. Our findings demonstrate that the PPy/SF conductive composite scaffolds with longitudinal guidance exhibit favorable properties for clinical use and promotes nerve regeneration and functional recovery.